(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article explores the complex interplay between gender and identity in 20th-century literary discourse. It examines how authors from diverse cultural and social backgrounds represented gender roles, challenged traditional norms, and negotiated personal and collective identities through literature. By analyzing key literary texts and theoretical frameworks, the study highlights the ways in which literature both reflects and shapes societal understandings of gender and identity. The research underscores the significance of considering historical, cultural, and political contexts in interpreting literary representations, offering insights into the evolving discourse on human experience and social constructs in the modern era.